A REVIEW: REMOVAL OF HEXAVALENT IONS FROM THE INDUSTRIAL WASTEWATER BY ACTIVATED CARBON AND NANO MATERIAL ADSORBENTS. (International Association of Biologicals and Computational Digest, 2022)
Industrial wastewater often contains chromium which has raised concerns towards hexavalent chromium as it is carcinogenic to animals as well as it can also cause genetic material alterations, kidney and liver damage, etc. Hence, there are many remedial methods which have been researched for removal of Cr(VI). Out of all the methods, this article talks more about activated carbon and nano material adsorbents used for the removal of hexavalent chromium. The capacity of various adsorbents are investigated for the removal of Cr(VI). The Langmuir and Freundlich adsorption models, which are in common use for describing sorption equilibrium for wastewater- treatment applications, are discussed. Apart from this, the adsorption dosage and capacity of disparate adsorbents are discussed with their kinetic and thermodynamic study. This review also includes the equilibrium time at which the maximum adsorption is achieved and optimum pH values for the maximum adsorption.
Keywords: Hexavalent chromium, wastewater, activated carbon, Nano material kinetics, thermodynamics, pH.